Pengenalan Bahasa Jepang Dasar Melalui Aplikasi Powtoon di SDN 01 Bandar Buat Padang - Nova Yulia; Hendri Zalman; Nora Fudhla; Lili Mulyani (Universitas Negeri Padang, 2023)
SDN 01 Bandar Buat is located in Lubuk Kilangan District, Padang, with an average number of students of 28 per class. At SDN 01 Bandar Buat, students can learn foreign languages according to their learning abilities. Studying a foreign language is very necessary to increase students' knowledge. Apart from English which has been studied since elementary school, other foreign languages will also be very beneficial if introduced from an early age, one of which is Japanese. In everyday life, we can find children's shows that use Japanese, such as the anime of Doraemon, Ultraman, and many others. Besides that, many Japanese songs are also sung by children. This indicates that Japanese is very familiar among children. SDN 01 Bandar Buat provides the opportunity to teach Japanese language and culture from an early age so that it can provide benefits and provide refresher knowledge in the midst of the lessons they have learned so far. Learning Japanese vocabulary for children aged 6-12 years is not easy, because it is something they have never done before. Teachers had to be creative and use interesting teaching strategies. Therefore, the team created an animated video using the Powtoon application to teach basic Japanese vocabulary. That video is in Indonesian and introduces Japanese vocabulary such as animals and plants.